Pengaruh Penerapan Model Pembelajaran Guided Discovery Learning Menggunakan Pendekatan Scientific Terhadap Hasil Belajar Siswa - Marchio Yosua Gratia Mamesah; Meyke Paat; Helen Joan Lawalata (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to determine the effect of the guided discovery learning model on student learning outcomes in class 12 using a scientific approach; in this research, the researcher used 2 learning methods, one of which is the conventional method; the researcher used 2 classes as samples, where each class was 15 students in each class, was coded as class A for the control class and class B for the experimental class. The research instrument used was a question in the form of a posttest.